PERAN USTADZ DAN USTADZAH TERHADAP KELANCARAN MEMBACA AL-QUR’AN: (STUDI KASUS SANTRI PESANTREN LANSIA NURUL IMAN KABUPATEN KARANGANYAR TAHUN 2022-2023) - Laili Nur Safitri; Suhadi; Yetty Faridatul Ulfah (Institut Islam Mamba'ul 'Ulum Surakarta, 2023)
This service provider is an organization under the auspices of the Nurul Iman Ta'lim Assembly Organization (MTNI) Karanganyar Regency This study aims to determine the effectiveness of the role of ustadz and ustadzah on the fluency of reading the Koran for elderly students at Nurul Iman Islamic Boarding School, Karanganyar Regency. In this study, a qualitative descriptive method was used, namely analyzing events and understanding existing phenomena, then creating a comprehensive and complex picture. The results of this study show how the role of an ustadz and ustadzah in the fluency of reading the Qur'an, inhibiting factors and supporting factors of ustadz and ustadzah on the fluency of reading the Qur'an of elderly students Nurul Iman. The results showed that there were several factors that became obstacles in improving the ability to read the Qur'an of elderly students, namely: 1) the motivation and interest of the elderly were not evenly distributed, 2) the lack of time to listen to the readings of the students one by one, 3) number of students. The supporting factors are: 1) board of caregivers, 2) motivation from the board, 3) personal factors, 4) family factors.